The Impact of Trust and Relationship Quality on Agricultural Cooperative Competitiveness - Hardana, Andrean Eka; Pratiwi, Destyana Ellingga (Department of Social Economy, Faculty of Agriculture , University of Brawijaya, 2023)
In recent years, supply chains have received attention from researchers and business practitioners. Many studies have been conducted to identify what factors affect supply chain competitiveness. The purpose of this study is to determine the effect of trust and relationship quality on the supply chain of agricultural cooperatives. This study used Structural Equation Modeling (SEM) as the analysis method and used primary data collected from dairy producers or farmers, management staff of Agricultural Cooperatives, and retailers involved in the dairy supply chain in Malang District. The conceptual model consisted of four hypotheses. The results show that the hypotheses are proven, which means that the variables of trust, communication quality, and relationship quality have a positive effect on the competitiveness of Agricultural Cooperatives. The results also show that the competitiveness of Agricultural Cooperatives simultaneously affects the trust of producers or farmers in Agricultural Cooperatives. This means that the higher the competitiveness of Agricultural Cooperatives, the higher the trust of producers or farmers towards Agricultural Cooperatives.